Length-weight relationship of four batoid species from the Pacific coast of Ecuador (Revista de Biología Marina y Oceanografía, 2022)
Length-weight relationships (LWR) were estimated for four species of batoids, Zapteryx xyster, Rostroraja equatorialis, Pseudobatos leucorhynchus and Gymnura crebripunctata, collected in Ecuadorian waters. Values of the allometric growth parameter (b) oscillated from 2.41 to 3.15. Pseudobatos leucorhynchus and G. crebripunctata exhibited isometric type growth, while Z. xyster and R. equatorialis showed negative and positive allometric growth, respectively. New records of minimum sizes were obtained for free-swimming R. equatorialis (7.8 cm TL) and G. crebripunctata (20.0 cm DW). Data obtained constitute a baseline for future management and conservation studies.